Diagnosis and management of solid pseudopapillary tumours of the pancrea - Chowdhury, MM; Khan, ZR; Hossain, MS (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):640-4 The abstract of this article is available on the PubMed website